EFL Teachers' Most Preferred Topics for the Syllabus of the Course "Teaching English to Young Learners" - Fatma Bulanık; Kürşat Cesur (Ömer Gökhan Ulum, 2020)
The course "Teaching English to Young Learners" has always been one of the most important courses of the ELT programs. Council of Higher Education changed the course hours from 4 hours each two hours of which were theoretical and practical to 3 hours which will basically deal with theoretical issues. As the course will cover some theoretical issues, this study aims to determine the most preferred topics to be taught in this course. The study follows mixed-methods sequential exploratory research design procedures. To form the questionnaire, ELT curriculums of 42 state universities were content analysed in the qualitative part of the study. Then, frequency tables and topics were composed. Eight topics were added to the 51 main topics after having an interview with two experts in the field. Lastly, the final table of topics for the questionnaire was formed and the questionnaire was created in Google Forms. In the quantitative part of the study, the data has been collected from 266 teachers, teacher educators and pre-service teachers from different cities of Turkey. The findings of this study showed that the participants think using visual items, games and songs, developing children's speaking skill and defining young learners and their characteristics are the most important topics for Teaching English to Young Learners. While participants' work status revealed some significant differences in their' topic preferences, there were no significant differences in terms of their teaching experience. At the end of the study, some suggestions for ELT and for further studies were provided.